A communicating artery between axillary and radial artery - a case report - N Komala; N Aruna (Wolters Kluwer Medknow Publications, 2012)
Variations in the branching pattern of axillary artery have been observed quite frequently. In a male cadaver aged around 45 years allotted for undergraduate dissection a communicating artery between axillary and radial artery was found on the right side during routine dissection. Such arterial variations are important for clinicians in angiographic examinations, removes ambiguity during diagnostic interventions and surgical procedures. Thereby it ensures competency and reduces complications in cardiac catheterization, pedicle flaps, arterial grafting etc.